The effect of polyvinyl fibers on metakaolin-based geopolymer mortars with different aggregate filling. (20th September 2021) - Sahin, Furkan; Uysal, Mucteba; Canpolat, Orhan; Cosgun, Turgay; Dehghanpour, Heydar
Highlights: Metakaolin-based three different aggregate-filled geopolymers were produced. The effect of PVA at three different rates on geopolymer composites was investigated. The mechanical behavior of geopolymers exposed to high temperature and freeze–thaw effects were investigated. SEM, XRD and FT-IR analysis were performed to investigate the microstructure of composites. Basalt sand filled geopolymers showed the best results. Abstract: Environmental pollution and high energy loss during cement production are important factors threatening concrete production. In order to prevent these problems, geopolymer binders have been accepted as an alternative to cement in recent years. In this study, recycled concrete aggregate, basalt sand, Rilem sand, blast furnace slag, and polyvinyl alcohol additive metakaolin based geopolymer mortars with 12 different mixtures were produced. Sodium hydroxide and sodium silicate were used for the activation of metakaolin. Mechanical properties of the produced specimens at 7, 28, and 56-days were examined. Also, ultrasonic pulse velocity, high temperature, density, and freeze–thaw tests of geopolymers were carried out. In addition, SEM, XRD and FT-IR analyzes were performed to examine the internal structures of geopolymer composites. According to the results obtained, polyvinyl alcohol fibers improved all properties of the specimens. In general, the best mechanical results were obtained for geopolymers containing 1.2% PVA. It has been observed that samples exposed to 800 °C maintained their stability. The 180 cycle freeze–thaw effect did not create any negative effects on the geopolymers. From the SEM analysis results, it has been confirmed that BS filled geopolymers have a more stable and dense structure than others. Satisfactory results were obtained for recycled concrete aggregate filled geopolymers. Intense quartz peaks were observed in the crystal structure XRD results of the samples exposed to a high temperature of 800 °C. In the FT-IR results, Si–O–H bonds and other expected peaks were observed and the precipitated product was determined as CaCO3 and calcium hydroxide (Ca(OH)2 ).